Defending virus infection through extrinsic apoptosis - Madihah Mohd Saudi; Nor A.M.; Cullen A.J.; Woodward M.; Noor H.M. (2024)
This paper discusses on the enhancement of the current Intrusion Detection System (IDS) based on Artificial Immune System called apoptosis. Nowadays network systems are required to be more secured since the virus is now growing stronger and more dangerous. Unfortunately, not all of the Intrusion Detection System (IDS) is effective enough to defend against viruses entering the network. In this paper, the researchers' propose a new enhanced IDS system that will defend the computer system from being attacked by viruses. By using apoptosis system as the basis of the enhancement, these IDS will work similar to the human defence system and solve the problem of the virus infection in the computer system. In addition, the researchers' have also improved the accuracy of IDS for detecting the virus by using this method. 2008 IEEE.